DINAMIKA USAHA PENGRAJIN REOG PONOROGO - Naning Kristiyana; Titi Rapini (Universitas Airlangga, 2017)
The prospect of Reog's handicrafts is more exciting because Reog's art is now one of the mainstays of Ponorogo tourism in national and even international scale. This study aims: Knowing the business conditions of craftsmen Reog Ponorogo, and Know the problems faced by the craftsmen Reog Ponorogo. Respondents of this study are Reog Craftsmen in Ponorogo. This research uses Quantitative Descriptive research method. The sample in this study population because the population is less than 100 ie 31 craftsmen. The data were collected by questionnaire. Data analysis in the field using descriptive and quantitative descriptive explorative format. The result of the research is known that the business of reog craft is mostly done downhill. Craftsmen have pioneered the business since about 10-20 years ago. Making a reog craft does not require higher education proved the largest number of artisans have a minimum of elementary education. The total workforce of each craftsman <20 workers. The highest level of labor education is SMP.Productions made monthly can reach the sales target because most of the production is based on orders from retailers. The market share of craft reog to foreign countries such as Malaysia, Korea, America, and others. The main problem of craftsmen is the difficulty in obtaining raw materials such as peacock, tiger skin, cow leather, cow tail, horse tail and high price of raw materials, capital problem.Keyword : Reog Craftsmen, Business Management, UKM Problems